Market Efficiency of Commercial Bank in Financial Crisis - Huang, Han-Ching; Su, Yong-Chern; Lin, Tze-Yi (International Journal of Economics and Financial Issues, 2016)
This study investigates commercial bank market efficiency in financial crisis. We employ a time-varying GARCH model because volatility matters in financial crisis. The empirical results show a significant positive relation between contemporaneous order imbalances and returns in convergence process toward efficiency. A direct linkage between volatility and order imbalances is examined by GARCH model. Surprisingly, a low connection exists between order imbalance and price volatility, implying that market makers are capable of mitigating commercial bank prices volatility in financial crisis. We develop an imbalance based trading strategy but fail to beat the market. A nested causality approach, which examines the dynamic return-order imbalance relationship during the price formation process, confirms the results. Keywords: order imbalance; market efficiency; commercial bank; financial crisis. JEL classification: G01; G14; G21